Lake Pontchartrain Basin bottom sediments and related environmental resources - Manheim, Frank T.; Hayes, Laura,|d1970-.; McFaul, E. J.; Geological Survey (U.S.). ([Reston, Va.] U.S. Dept of the Interior, U.S. Geological Survey, 2002)
Focuses on geological framework and sedimentary processes of Lake Pontchartrain Basin. Scientific Research and Assessments section features historical information on area; shipboard, field, and remote sensing studies; and a comprehensive sediment database with geological and chemical discussions of region. Multimedia Tools and Regional Resources section includes Geographic Information System (GIS) tools and data, video demonstrating vibracore sampling techniques, and abstracts from four Basics of Basin symposia
System requirements for PC: Pentium (Pentium II highly recommended); Windows 95 or greater (Windows 98 or better highly recommended); color monitor; VGA adaptor; hard disk; CD-ROM drive
System requirements for Macintosh: Power Mac (G3 or better highly recommended); System 8 (System 9 or better highly recommended); color monitor; hard disk; CD-ROM drive
Keywords: Lake sediments -- Louisiana -- Pontchartrain, Lake, Watershed; Sedimentation and deposition -- Louisiana -- Pontchartrain, Lake, Watershed; Geology, Stratigraphic -- Holocene